Experimental study on risk analysis of gas explosion in a steeply inclined longwall gob: a case study of Dongxia Colliery. (28th February 2022) - Su, Hetao; Li, Yunzhuo; Liu, Yingke; Song, Xiaolin; Lv, Jiang
An explosive concentration can occur during mining due to the irregularity of methane emission and ventilation processes in the working face, making the explosion risk uncontrollable. This paper aimed at characterising the gas explosion risk in a steeply inclined longwall gob (52°). A physical simulation on air-gas mixture migration was conducted to analyse the spatial distribution and explosibility of the air-gas mixture in a steeply inclined gob from Dongxia colliery using a scaled-down experimental set-up. Results showed that the methane accumulation zone focused on the air return side for the horizontal ventilation and ascensional ventilation (+52°), which mainly caused by the rising phenomenon of methane. Increasing ventilation velocity played an important role on reducing the risk of gas explosion under the horizontal ventilation and ascensional ventilation. However, it was ineffectual under the descensional ventilation (-52°). Furthermore, an index was proposed to quantitatively evaluate the gas explosion risk. [Received: February 18, 2020; Accepted: January 20, 2021]